Strategi Pengembangan Sosial Emosional Anak Berkebutuhan Khusus: - Hartin Kurniawati; Rosidah Rosidah; Ernawati Ernawati (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Children show an increased ability to reflect emotions, when they are 4 to 5 years old. They also came to understand that the same incident can evoke different feelings in different people. They maintain an increased awareness so that they are able to manage their emotions and meet social standards. The objectives to be achieved in this study were to determine the stages of achieving the social emotional development of children with special needs and how the social emotional development strategies of children with special needs at PAUD Pondok Anak Pertiwi. The research method used is a qualitative approach. In conducting research, data sources are needed, and data collection uses primary and secondary sources. Primary sources are data sources obtained directly from informants, in this case the principal and homeroom teacher and psychologist, as well as 3 (three) children with special needs aged 4-5 years who are made cases. Meanwhile, secondary data is in the form of several documents required for completeness of research data. The data analysis technique used is descriptive qualitative through data reduction, data presentation and conclusion drawing. The results showed: 1. The results of the level of achievement of social emotional development for children with special needs can be seen from prosocial behavior by working with friends, willing to queue and take turns playing, being able to communicate with people they meet verbally or non-verbally. It can also be seen in being able to control normal emotions by showing separation behavior when not crying, being easily persuaded during tantrums and showing pride in the work by smiling, laughing and jumping around as a feeling of pleasure. 2. The learning strategy carried out in developing the social emotional of children with special needs is through habituation activities. Habit is carried out at school and continues to be stimulated by parents at home, such as greeting, greeting, washing hands, taking out trash, queuing, and others. The success of this habituation depends on a stimulating environment, consistent collaboration between teachers and the environment at school and parents at home. Keywords: Strategy, Social Emotional, Children with Special Needs